Adopting General English or Academic English (BICS/CALP) in University Students' Textbooks: A Case Study of Textbooks Analysis (Journal of the College of Basic Education, 2022)
This research includes two parts: a comparison and an analysis. Each part has a different aim. The first part, which represents the core part of this paper, aims to show the main differences between two variation of English, i.e. Basic Interpersonal Communication Skills (BICS) which is commonly known as General English and Cognitive Academic Language Proficiency (CALP) which is commonly known as Academic English. The second part of the present study, however, is set to carry out an in-depth descriptive textbook analysis for textbooks taught in the first year of the BA program in English department at AL-Mustarnsiriyah University in order to show whether they are suitable for academic environment or not and which kind of English language is included in the textbooks under analysis. Qualitative descriptive analyses are used to assess four university textbooks based on Zhang (2017) categories. The results indicate that they are not really appropriate for teaching/learning English for academic purpose, especially in departments using English as medium of instruction. Such departments should provide their students with textbooks designed and organized to teach Academic English rather than General English. Finally, conclusions and recommendations have been presented.(Keywords: BICS, General English, CALP, Academic English, Case Study, Textbooks Analysis)